Electrochemical investigation of copper passivation kinetics and its application to low-pressure CMP modeling - Li, Jing; Liu, Yuhong; Wang, Tongqing; Lu, Xinchun; Luo, Jianbin (Applied surface science, 2013)
▸ The copper passivation kinetics is studied by the chronoamperometry technique. ▸ A model based on the passivation kinetics is proposed for low-pressure CMP. ▸ The mechanical effect dominates the material removal at pH 4. ▸ It is a chemical dominant process at pH 10 during low-pressure CMP. During the process of chemical mechanical planarization (CMP) of copper interconnection in ultra large scale integration (ULSI), copper passivation plays a critical role in material removal. The kinetics of copper passivation in glycine solutions containing BTA was studied by the chronoamperometry technique. The results showed that the current density transients followed with a double-exponential decay, including both non-faradaic double layer charging and faradaic reaction effects. Furthermore, a model based on the passivation kinetics was proposed for low-pressure CMP. Combining the model and the experimental results, the material removal mechanism was analyzed. The mechanical effect dominated the material removal at pH 4, while it was a chemical dominant process at pH 10.